Exploring Global Research on Fashion Pattern Innovation through Computer-Aided Design: A Bibliometric Approach - Widi Aliffa Izzara; Ernawati Ernawati; Weni Nelmira; Muhammad Giatman (AL-ISHLAH: Jurnal Pendidikan, 2025)
The fashion industry is undergoing a digital transformation, particularly in patternmaking, where traditional methods face limitations in efficiency, precision, and scalability. Computer-Aided Design (CAD) has emerged as a key technology, yet global research on CAD-based fashion pattern innovation remains fragmented and underexplored. This study adopts a bibliometric approach using the PRISMA protocol to systematically analyze 124 Scopus-indexed publications from 2000 to 2024. Analytical tools such as Biblioshiny (R Studio) and Microsoft Excel were employed to map research trends, contributors, citation impact, and thematic developments. Findings indicate a moderate annual growth rate of 1.7% in publications. China, the United States, and France are the most active contributors, with journals like Computer-Aided Design and Applications serving as primary outlets. Highly cited studies emphasize virtual simulation, 3D editing, and anthropometric modeling. Co-occurrence analysis reveals dominant themes such as CAD, fashion design, virtual reality, and automation, indicating strong interdisciplinary convergence. This study contributes by mapping two decades of research, identifying global collaboration patterns, and highlighting emerging topics. The results offer practical implications for curriculum development, research prioritization, and digital innovation in the fashion industry. Despite limitations in data scope and sample size, the study establishes a foundational understanding of CAD’s role in pattern innovation and calls for broader data inclusion in future research.